P104 Gene expression profiles in inflamed colonic biopsies from newly diagnosed Crohn's disease and ulcerative colitis patients differ depending on the age at diagnosis. (16th January 2018) - Verstockt, S; Verstockt, B; Van Bouwel, J; Meert, W; Cortes Calabuig, A; Brys, V; Ballet, V; Glorieus, E; De Decker, M; Van Assche, G; Hindryckx, P; Ferrante, M; et al.
Abstract: Background: Crohn's disease (CD) and ulcerative colitis (UC) are the most common forms of inflammatory bowel disease (IBD), both of unknown aaetiology. Clinical phenotypes are heterogeneous, partly depending on age at diagnosis. In this study we aimed to define the molecular profile of newly diagnosed IBD patients naïve for biologicals and immunosuppressives, and if this differs depending on the age at diagnosis. Methods: Inflamed colonic biopsies were obtained from 23 CD (median age 24.0 (16.2–62.8) years; 35% male; 5 L2/18 L3) and 16 UC (median age 31.5 (16.7–69.0) years; 29% male; 7 E2/9 E3) patients within 6 months after diagnosis. All patients were naïve for biologicals and immunosuppressives, and without previous IBD-related surgery. Biopsies from 15 non-IBD controls (median age 35.7 (20.6–68.3) years; 47% male) were used to age-match with each patient group. Single-end RNA sequencing was performed using Illumina HiSeq4000. Normalisation and differential expression was done using DESeq R package. A fold change >2.0 and adjusted p < 0.05 were considered biologically significant. Pathways were analysed with IPA. Results: Comparative analysis identified 632 (516 up, 116 down) differentially expressed genes between CD patients and age-matched controls; and 3796 (2542 up, 1254 down) between UC patients and matched controls; 581 genes were different in both CD and UC. Common upstream regulators of overlapping genes are STAT1, IFNγ, IFNα, and TNF. Pathway analysis showed that Th1/Th2 activation (e.g. STAT1, MHC-II HLAs) was enriched in CD and UC, while phagosome formation (e.g. FCGR2A/B, TLRs) and agranulocyte adhesion/diapedesis (e.g. MMPs) were UC-specific. While in CD there was a fairly small difference between younger (≤30 years, n = 16) and older-onset (>30 years, n = 7) patients (58 and 110 dysregulated genes, overlap of 21), younger (≤40 years, n = 11) UC patients showed more dysregulation than older-onset (>40 years, n = 5) UC patients: 3550 vs. 1722 genes, with an overlap of 1441. This seems to also reflect differences in disease severity between younger and older-onset, with 64% of younger UC exhibiting extended disease (E3) compared with 40% in the older group. Genes unique for younger UC are mainly involved in "LPS/IL-1 mediated inhibition of RXR" (eg. TNF, TLR4), while those specific for older UC were enriched for "role of macrophages, fibroblasts, and endothelial cells in rheumatoid arthritis" (eg. VCAM, TLR10). Conclusions: There is a strong mRNA dysregulation in newly diagnosed CD, and even more in newly diagnosed UC. Younger-onset UC shows a prominent mRNA dysregulation compared with older-onset. This difference most likely reflects differences in disease severity, although this needs to be further established.